Determinant Faktor Yang Berhubungan Dengan Perilaku Pencegahan Komplikasi Pada Hipertensi - Fahrur - Rozi; Eliza Zihni Zatihulwani; Gevi Melliya Sari (FORIKES, 2021)
Background: Hypertension is a disease that rarely shows severe complaints but can lead to severe complications because it is also known as a silent killer disease. Objective: To determine the factors associated with the behavior of preventing complications in hypertension. Methods: This study used a quantitative research design with a cross-sectional study design. The number of samples in this study was 272 patients with hypertension using the purposive sampling technique. The questionnaire used in this study was a knowledge questionnaire about hypertension and a complication prevention behavior questionnaire. Analysis of data using the Spearman Rank Test correlation. Results: The results of data analysis showed the relationship between the level of knowledge about hypertension and the behavior to prevent complications of hypertension obtained a value of ρ value of 0.000